Hospital dentistry: a brief review (Research, Society and Development, 2021)
This study aims to carry out a literature review of the narrative type on the performance and duties of the dental surgeon in the hospital environment. This is a narrative review of the literature, analyzing papers published in SCIELO (Scientific Electronic Library Online) and LILACS (Latin American and Caribbean Literature in Health Sciences) with the keywords "Hospital, Dentistry, Intensive Care Unit". The insertion of the dental surgeon in the team multidisciplinary approach to hospitals contributes to the treatment of hospitalized patients, given the existence of a relationship between oral and general health, so the duties of these professionals mainly in Intensive Care Units corroborate for the maintenance of oral health, enabling quality of life from an integral view Therefore, it is extremely important to qualify in hospital dentistry in the training of professional dental surgeons.